A New Device for Remote Monitoring of Vital Parameters in Acromegalic Patients: Pilot Study - Costa, Denise; D'Amico, Tania; Mercuri, Valeria; Schiaffini, Riccardo; Gargiulo, Patrizia (Endocrine, metabolic & immune disorders drug targets, 2022)
Acromegaly is a rare disease that results from growth hormone (GH) excess. Diabetes mellitus, hypertension,cardiomyopathy, and obstructive sleep apnoea syndrome( OSAS) are frequent complications. Identify a useful system to obtain a reliable remote monitoring of glucose and the most important vital parameters in the acromegalic subjects. Sixteen acromegalic patients (from 30 to 73 years old) were enrolled. We provided health monitor devices to the patients for continuous acquisition of physiological signals including twelve-lead electrocardiography (EKG) and nocturnal SpO2. At the same time, we applied on the same patients the blinded continuous glucose monitoring system(CGMS). The lowest saturation peaks at night (<80%) were achieved in patients with a known diagnosis of OSAS. A positive correlation was demonstrated between the lowest oxygen saturation values and the CGM peaks (pV <0,0001) and between the average values of oxygen saturation and CGM (pV<0,0003). Patients with a previous diagnosis of OSAS, obtained by polysomnography, showed on the multiparametric monitor recordings superimposable to their known condition. Instead we noticed a discordance in the two EKG recording: the wireless mode showed an irregular rhythm in 5/16 patients, which was not confirmed by the recording mode with cables. The health monitor device associated with CGM may be a new useful and versatile tool for fragile patients who can self-manage remote monitoring, and for physicians who can obtain real-time information for the clinical and therapeutic management of patients. It is also a useful tool for the follow-up of patients with OSAS. Moreover, once the interference of the OSAS is excluded, the CGM allows us to obtain a more reliable and accurate diagnosis of DM.